Free School Meals Policy: Lessons Learned from Around the World for Indonesia - Saddam Rassanjani; Isramatur Rahmi (Faculty of Social and Political Sciences, Universitas Diponegoro, 2025)
This research examines the implementation of free school meals policies worldwide. Based on the campaign promises of Prabowo Subianto and Gibran Rakabuming Raka, this program is expected to address four main issues: stunting, improving nutrition, enhancing academic achievement, and alleviating extreme poverty. The research adopts a literature review approach, utilising Scopus-indexed sources alongside bibliometric and content analysis to examine global trends, impacts, and challenges associated with such programs. The findings reveal that free school meal programs make a significant contribution to students’ nutritional status, cognitive development, and socioeconomic well-being. However, challenges related to financial sustainability, equitable distribution, and food waste management remain critical obstacles to practical implementation. Lessons from various countries suggest that successful programs require strong political commitment, efficient resource allocation, and multi-sectoral collaboration. In the Indonesian context, implementing a large-scale free school meal initiative demands careful planning and stakeholder engagement to ensure sustainability and effectiveness. This study concludes that while the program holds substantial potential to address pressing social challenges, further research is necessary to evaluate its feasibility, cost-effectiveness, and long-term impact in Indonesia. A comprehensive approach involving policymakers, educators, health experts, and local communities is recommended to support the successful implementation of this initiative, ensuring that it aligns with national development goals and international best practices.